The Influence of Shanxi Merchant Culture on Brand Culture Management - Tantai, Jiazi; Phtochanachan, Dr.Sarana; Nukulkij, Dr.Dheetawat (Journal of Dhamma for Life, 2023)
This research delves into the rich and enduring culture of Shanxi merchants, which flourished during the Ming and Qing dynasties. The remarkable success of Shanxi merchants can be attributed to their distinctive management ethos, characterized by principles of justice, honesty, and adaptability. The primary objective of this study is to unveil the profound interplay between Shanxi Merchant Culture and Brand Culture Management, with a specific focus on tea brands. It seeks to unearth the elements of Shanxi Merchant Culture that play a pivotal role in shaping the image of tea brands and scrutinize how the spiritual tenets inherent in Shanxi Merchant Culture exert influence on contemporary tea brand culture. To achieve these objectives, a mixed-methods approach is adopted, combining qualitative analysis through interviews and quantitative analysis using questionnaires. The research collects and meticulously analyses data, ultimately culminating in the development of a structural equation model. The study's participants predominantly encompass members of the Shanxi Tea Association, experts from the Shanxi Merchant Culture Research Institute, stakeholders from local tea cultivation and processing enterprises in Shanxi, academic professionals, and relevant industry experts. The research findings, synthesized through rigorous data analysis, substantiate the positive impact of three core dimensions of Shanxi Merchant Culture – Economic Value, Spiritual Value, and Social Value – on the facets of Brand Culture Management. These dimensions exhibit the potential to exert a favourable influence on Brand Culture Management, mediated through the intermediary variables of Brand Communication and Brand Value. From a holistic perspective, this study underscores the transformative role of Shanxi Merchant Culture within the tea industry. It illuminates how this cultural legacy equips tea enterprises with strategic insights, foundational values, and multifaceted dimensions that enrich the landscape of Brand Culture Management. Consequently, this cultural influence not only imparts valuable perspectives but also offers a robust conceptual framework that propels the development of tea brands in a dynamic and competitive market.